Retention of fish biodiversity in a mixed-use agroecosystem in Cambodia - Tilley, Alexander; Freed, Sarah; Cagua, E. Fernando; Longobardi, Lorenzo; Sean, Vichet; Mith, Samonn; Kim, Miratori; Kura, Yumiko (Springer, 2023)
Fisheries of the Mekong Basin are crucial to regional food security. They rely on seasonal monsoon rains that inundate rice fields and reconnect water bodies. Species assemblages vary over time and space, but infrastructure developments and climate change are negatively impacting the timing and magnitude of the flood pulse as well as fish migration routes and populations. In lowland rice field landscapes of Cambodia, community fish refuges (CFRs) are used to maintain fish abundance and biodiversity, with varying success. There is little knowledge of the drivers of this variation to guide management interventions. We used beta diversity to explore the effectiveness of 40 CFRs in maintaining species abundance and diversity during the dry seasons from 2012 to 2015. Results show CFR connectivity to the floodplain is important and suggest the type of inlet/outlet influences fish retention. CFRs connected to a large area of rice fields during the wet season had lower losses in species abundance through the dry season. However, large CFRs, or those part of a larger body of water, had higher losses in species abundance. Key design features of CFRs must be coupled with strong management capacity to guide the conservation and fisheries strategy in the Mekong Basin.